2017
DOI: 10.1111/1759-7714.12557
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary pleomorphic carcinoma with few PD‐1‐positive immune cells and regulatory T cells that showed a complete response to nivolumab

Abstract: Pulmonary pleomorphic carcinoma has been shown to respond remarkably to PD‐1 inhibitors; however, the biomarkers for this therapy have not been fully proven. We report a case of pulmonary pleomorphic carcinoma with overexpressed PD‐L1, in which a complete response to nivolumab was sustained for >14 months. Immunohistochemical analysis revealed few PD‐1+ immune cells and regulatory T cells in the tumor, in addition to predominant infiltration of CD8+ cells and macrophages. Our findings suggest that the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…26 In addition, disease progression during first-line chemotherapy for NSCLC was reported to correlate with high levels of circulating MDSCs. 27 Combining these findings with the results of our previous studies, 4, 25,28 we hypothesize that both the exhaustion levels of cytotoxic T cells and interference with myeloid cells may affect the efficacy of nivolumab and subsequent salvage chemotherapy (Fig 3).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…26 In addition, disease progression during first-line chemotherapy for NSCLC was reported to correlate with high levels of circulating MDSCs. 27 Combining these findings with the results of our previous studies, 4, 25,28 we hypothesize that both the exhaustion levels of cytotoxic T cells and interference with myeloid cells may affect the efficacy of nivolumab and subsequent salvage chemotherapy (Fig 3).…”
Section: Discussionsupporting
confidence: 76%
“…A hypothetical model of the possible underlying mechanisms of nivolumab and subsequent salvage chemotherapy, based on the results of our previous and present studies . PD‐1 expression levels on tumor‐infiltrating lymphocytes (TILs) probably indicate the exhaustion of lymphocytes.…”
Section: Discussionmentioning
confidence: 88%
“…We reported that a case of lung cancer regressed spontaneously and subsequently relapsed with an increase in the number of Tregs in the circulation . We also reported that lung cancer cases showing a remarkable response to nivolumab contained < 5% Tregs in the tumor . Tregs inhibited nivolumab‐stimulated release of interferon‐γ from effector T cells in vitro .…”
Section: Discussionmentioning
confidence: 90%
“…21,22 We also reported that lung cancer cases showing a remarkable response to nivolumab contained < 5% Tregs in the tumor. 23,24 Tregs inhibited nivolumab-stimulated release of interferon-γ from effector T cells in vitro. 25 Although PD-1 blockade did not affect the function of Tregs, 26 several anti-cancer drugs are known to reduce the number of Tregs and restore the activity of effector T cells.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, there is a trend for improving treatment results by using immune checkpoint inhibitors in combination with chemotherapeutic drugs. Recently, there have been some case reports of patients with polymorphic cancer responding to immune checkpoint inhibitors (9-13), while others have failed (9)(10)(11)(12)(13). We herein report a case of pleomorphic carcinoma of the lung treated with pembrolizumab and platinum-containing chemotherapy.…”
mentioning
confidence: 89%